P.089 Characteristics of children with cerebral palsy secondary to intrapartum asphyxia in the post-therapeutic hypothermia era. (June 2022) - Pekeles, H; Al Amrani, F; Perez-Morgui, M; Wintermark, P; Shevell, M
Abstract : Background: We explored the profile of children with cerebral palsy (CP) secondary to intrapartum asphyxia (IAP), who were treated with therapeutic hypothermia (TH). We compared neonatal characteristics between children treated with TH with a mild vs severe CP. Methods: We collected perinatal and outcome measures of children treated with TH for IAP. We searched the literature for characteristics of children prior to TH to compare to our cohort. We subdivided our cohort into mild vs. severe CP and compared neonatal characteristics to identify predictors of severe phenotype. Results: We found more children with severe (19/30) compared to mild CP (11/30). Post-TH era children leaned towards a more severe phenotype compared to prior to TH. Children with severe CP had significantly higher mean birth weight, lower 5- and 10-minute Apgars, and more often white matter with associated deep gray matter injury or near-total injury pattern on MRI compared to the mild phenotype group (all p<0.05). Conclusions: Our data leaned to a more severe CP in cooled children compared to pre-TH. Birthweight, 5- and 10-minute Apgars and MRI findings were significantly different between our mild vs severe group. Our findings can guide clinicians how to better weigh these factors when counseling parents in the neonatal period.